Analisis Deskriptif Penerapan Pasal 378 KUHP dalam Dakwaan Kesatu: Studi Kasus Tindak Pidana Penipuan pada Putusan Perkara Nomor 456/Pid.B/2018.PN.Jkt.Pst - Laia, Pesman; Yusuf, Hudi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Criminal fraud is one of the violations that frequently occur in society and is a primary concern for law enforcement agencies. This crime involves various methods, requiring extra efforts to prove, and is influenced by factors such as poverty, environment, and the desire to obtain money without hard work. This article discusses fraud in the context of Article 378 of the Indonesian Criminal Code (KUHP), which regulates this offense. The research analyzes the indictment against Magda Safrina, a company director, who used another person’s certificate as collateral for an international event. The aim is to explain the elements of fraud under Article 378 KUHP, especially those related to the use of false identities, deception, and a series of lies. Additionally, the study examines the criminal legal perspective on fraud and forgery and the effectiveness of implementing Article 378 KUHP in the Indonesian judicial system. The research method employed is a case study with normative and conceptual legal approaches. The findings indicate that despite the frequent application of Article 378 KUHP, there are disagreements and imperfections in its implementation. Economic factors affect the effectiveness of legal enforcement. Therefore, corrective measures are necessary, including intensive training for judges and prosecutors, improving the quality of investigations, and reforming the criminal justice system.